1992
DOI: 10.1093/ajcn/56.3.559
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of the water-soluble vitamins thiamin, ascorbic acid, and folic acid in serum and cerebrospinal fluid of healthy individuals

Abstract: Thiamin, thiamin monophosphate, ascorbic acid, and folic acid were determined in serum and cerebrospinal fluid (CSF) in 31 outpatients who underwent a myelography because of back-pain. All subjects were otherwise healthy. The CSF concentration (mean +/- SD) was 8.6 +/- 3.9 nmol thiamin/L, 16.9 +/- 8.3 nmol thiamin monophosphate/L, 133 +/- 58.8 mumol ascorbic acid/L, and 44.9 +/- 13.2 nmol folic acid/L. The CSF-serum ratio was 2.1 +/- 0.8 for thiamin, 8.3 +/- 4.3 for thiamin monophosphate, 3.0 +/- 1.4 for ascor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…1 when serum folate achieves high values ( 1 35 nmol/l). Among all 205 consecutive subjects, the lowest value of the R CSF/S was 0.0495 and the mean value of the folate gradient R CSF/S was 2.13 8 0.93, in agreement with previous study results [18,20,21] .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…1 when serum folate achieves high values ( 1 35 nmol/l). Among all 205 consecutive subjects, the lowest value of the R CSF/S was 0.0495 and the mean value of the folate gradient R CSF/S was 2.13 8 0.93, in agreement with previous study results [18,20,21] .…”
Section: Resultssupporting
confidence: 92%
“…It seems reasonable to presume that lack of folate can cause cerebral lesions also in adults [17] . There are a few other studies that have dealt with the concentration of folate in CSF [10,[18][19][20][21] and a few earlier works concerning the relation between CSF folate and dementia [22][23][24] . Shaw et al [22] found that CSF folate did not rise as serum folate did when severely demented, folate-deficient patients were substituted with folate, nor was there any clinical effect of the folate treatment.…”
Section: Csf/serum Folate Gradient In Different Dementiasmentioning
confidence: 99%
“…Of NAALADase's known substrates, only NAAG, ␥-glutamylglutamate, and folates have been detected in neural tissue, and the apparent affinity of ␥-glutamylglutamate for NAALADase and concentrations of folates in the extracellular space of the central nervous system are considerably lower than those of NAAG (1,20,47,48). NAALADase's regional and developmental expression in brain correlate with levels of NAAG, suggesting that the two are functionally related (8,21,49).…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] Plasma and tissue levels of total nitrite (NO 2 Ϫ ) plus nitrate (NO 3 Ϫ ), known as NOx, were measured by HPLC after reduction of total NOx to NO 2 Ϫ , as described previously. 26 Plasma levels of asymmetrical dimethyl arginine (ADMA), an endogenous NOS inhibitor, were determined by using HPLC as described previously.…”
Section: Plasma and Tissue Biochemical Measurementsmentioning
confidence: 99%